Basis of Shoulder Nerve Entrapment Syndrome: An Ultrasonographic Study Exploring Factors Influencing Cross-Sectional Area of the Suprascapular Nerve - Wu, Wei-Ting; Chang, Ke-Vin; Mezian, Kamal; Naňka, Ondřej; Lin, Chih-Peng; Özçakar, Levent (Frontiers in Neurology, 2018)
As changes in nerves' shape and size are common ultrasonographic findings of entrapment neuropathy, measurement of the nerve cross-sectional area (CSA) becomes the mostly used indicator to differentiate normality from pathology. Recently, more US research has been conducted to measure the shape of the suprascapular notch and the diameter of the suprascapular nerve. Because the suprascapular nerve is paramount for various shoulder disorders, the present study aims to establish normal values of suprascapular nerve sizes at different levels as well as to investigate potential influence of participants' characteristics on the CSA measurements. The present study used a cross-sectional design investigating the CSA values of the suprascapular nerve from the supraclavicular region to spinoglenoid notch. We employed the inside-epineurium and outside-epineurium methods to quantify CSA of cervical roots (C5 and C6) and the suprascapular nerve on US imaging. Univariate comparisons of nerve sizes among different age and gender groups were carried out. Multivariate analysis was performed to analyze the impact of participants' characteristics on nerve CSA. Repeated measurement analysis of variance was conducted to examine segmental variations of CSA of the suprascapular nerve from its origin to infraspinatus fossa. Our study included 60 healthy adults with 120 shoulders and had three major findings: (1) the inside-epineurium method was more reliable than the outside-epineurium approach for CSA measurements due to higher intra- and inter-rater reliability, (2) women had smaller sizes for cervical nerve roots and for the most proximal segment of the suprascapular nerves, and (3) using the outside-epineurium method, the suprascapular nerve CSA was larger in its distal division than the portion proximal to the mid-clavicular line. In conclusion, the inside-epineurium method has better reliability for nerve CSA assessment but the outside-epineurium method is needed for quantifying the size of distal suprascapular nerve. Gender difference in CSA values should be considered during evaluation of the most proximal nerve segment. Using the outside-epineurium method, the distal suprascapular nerve would be estimated larger than its proximal portion and the segmental discrepancy should be not misinterpreted as pathology.